Green Energy Technologies: A Key Driver in Carbon Emission Reduction - Wenten, I Gede; Khoiruddin, Khoiruddin; Siagian, Utjok Welo Risma (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
This paper explores the vital role of green energy technologies in mitigating carbon emissions and advancing sustainable energy transition. It emphasizes the significance of green energy in reducing the carbon footprint, delves into the environmental consequences of carbon emissions, and analyzes the mechanisms through which green energy contributes to carbon reduction. This paper discusses technological advancements across various renewable energy sources, including solar, wind, hydroelectric, biomass, geothermal, tidal, wave, nuclear, osmotic, and salinity-powered energy generation. It also examines emerging green energy technologies, identifies barriers to adoption, offers an Indonesian perspective, and provides recommendations for a greener energy future. Overall, this paper offers a comprehensive exploration of green energy's transformative potential in combatting climate change and promoting sustainable development.